Design and numerical simulation of a self-adaptive variable-diameter robot for in-pipe non-destructive inspection. Issue 2 (May 2020) - Ling, Zhangwei; Yu, Xuefen; Yan, Sunting; Chen, Yonggui
Abstract: This paper presents a design method and numerical simulation result of an smart in-pipe inspection robot with capability of adjusting its diameter to adapt to pipelines of non-constant inner diameter insensitive to non-smooth imperfect inner surface due to corrosion or erosion. A variable-diameter component consisting of a motor, gear wheels, a screw and nut drive system and a bar linkage is introduced to achieve this self-adaption. Moreover this paper presents a force-balance analysis by virtual displacement principle relating the normal force and internal spring force and conducts a numerical simulation of dynamic process of a 3D mechanical model across diameter-varying sections in horizontal, vertical manners and records transient inner spring force. The paper has significant reference merit for engineering application to ensure safe operation of pipelines.